Candida albicans exhibit two classes of cell surface binding sites for serum albumin defined by their affinity, abundance and prospective role in interkingdom signalling. - Claire Teevan-Hanman (Public Library of Science (PLoS), 2021)
Serum albumin binding to the yeast form of Candida albicans is described. Two populations of binding site are identified using two complementary spectroscopic techniques: an extrinsic fluorescent probe, 3-hexa-decanoyl-7-hydrocoumarin ([HEXCO) added to the C. albicans yeast cell surface that records the electrostatic surface potential and so responds to the surface binding of serum albumin and secondly a light scattering technique that reveals how albumin modulates aggregation of the yeast population. The albumin binding sites are found to possess different binding affinities and relative abundance leading to different total binding capacities. These are characterized as a receptor population with high affinity binding (Kd ~ 17 μM) but relatively low abundance and a separate population with high abundance but much lower affinity (Kd ~ 364 μM). The low-affinity binding sites are shown to be associated with the yeast cell aggregation. These values are found be dependent on the C. albicans strain and the nature of the culture media; some examples of these effects are explored. The possible physiological consequences of the presence of these sites are speculated in terms of evading the host's immune response, biofilm formation and possible interkingdom signaling processes.